2015
DOI: 10.1111/gfs.12210
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stage of growth and additives with or without cellulase on fermentation andin vitrodegradation characteristics ofLeymus chinensissilage

Abstract: This study evaluated the effects of different combinations of added lactic acid bacteria and cellulase applied at two growth stages on chemical composition and in vitro rumen digestibility of Leymus chinensis silage. Fresh grass was harvested at early heading stage (S1) and late heading stage (S2), respectively, and ensiled with five additives: 200 U cellulase (C) kg−1 fresh matter (FM), 1 × 105 colony‐forming units (cfu) Lactobacillus plantarum (LP) g−1 FM, 1 × 105 cfu Lb. casei (LC) g−1 FM, LP+C, LC+C and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
41
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 50 publications
10
41
0
1
Order By: Relevance
“…Generally, 1 × 10 5 cfu g −1 LAB and 60–70 g kg −1 DM WSC in the material are required for successful ensiling (Smith, ; Weinberg, ). In line with our previous studies (Zhang, Yu et al., ; Zhang et al., ), a relatively low WSC content and LAB count in L. chinensis were observed in the present study. The WSC content was 43.9 g kg −1 DM, and the LAB count was lower than 1 × 10 5 cfu g −1 , which is unfavourable for a successful fermentation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Generally, 1 × 10 5 cfu g −1 LAB and 60–70 g kg −1 DM WSC in the material are required for successful ensiling (Smith, ; Weinberg, ). In line with our previous studies (Zhang, Yu et al., ; Zhang et al., ), a relatively low WSC content and LAB count in L. chinensis were observed in the present study. The WSC content was 43.9 g kg −1 DM, and the LAB count was lower than 1 × 10 5 cfu g −1 , which is unfavourable for a successful fermentation.…”
Section: Discussionsupporting
confidence: 93%
“…Silages were sampled and chemical; microbial compositions were analysed according to Zhang, Yu, Yang, and Na () and Zhang et al. ().…”
Section: Methodsmentioning
confidence: 99%
“…Both positive and no effect results have been reported when attempting to improve silage quality with cellulase (Sheperd & Kung 1996;Zhang et al 2015). Both positive and no effect results have been reported when attempting to improve silage quality with cellulase (Sheperd & Kung 1996;Zhang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sheperd and Kung (1996) reported that cellulase has no effect on fermentation acids or nitrogenous compounds in silage at any maturation level, regardless of dose. Zhang et al (2015) reported that a cellulase additive decreases pH and ammonia-N content of Chinese Leymus silage. Zhang et al (2015) reported that a cellulase additive decreases pH and ammonia-N content of Chinese Leymus silage.…”
Section: Discussionmentioning
confidence: 99%
“…Then the filtrate was centrifuged at 20 000 g for 10 min and reserved for fermentation acids and ammoniacal nitrogen (NH 3 -N) analyses. Lactic acid (LA), acetic acid (AA), PA and butyric acid (BA) were determined according to Zhang et al (2016b). NH 3 -N was determined by the phenol-hypochlorite colorimetric method according to Broderick and Kandg (1980).…”
Section: Chemical and Microbial Analysesmentioning
confidence: 99%